Implikasi Pengaturan Hukum Kepemilikan Asing Atas Saham Dalam Perbankan Nasional - Sautaqi, Izfahany Mahesa; Apriani, Rani (Peneliti.net, 2025)
The increase in share ownership by foreign nationals was triggered by the existence of regulations in the form of laws which provided an opportunity for foreigners to own shares of up to 99%. This provision aims to facilitate banks in improving their capital structure. Using normative juridical research methods, it is concluded that the legal regulation of foreign ownership of shares in national banks has positive implications, namely the creation of good bank corporate governance and an increase in bank performance. However, it also has a negative implication, namely when banks can ultimately be controlled by foreigners who tend to be more profit-oriented than efforts to increase people's welfare, as well as the risk of capital flight abroad during a crisis.